THE IMPORTANCE OF INCLUSIVE EDUCATION IN IMPROVING EDUCATION QUALITY - Javohir Ismoil ugli Abdullayev (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: This study examines the significant role of inclusive education in enhancing the quality of education through its impact on academic achievements, social integration, emotional well-being, and professional development of teachers. Research indicates that inclusive environments not only improve academic outcomes and cognitive skills but also foster social competence and emotional health. Additionally, inclusive education necessitates continuous professional development for teachers, enhancing their teaching practices and collaborative efforts. Despite challenges such as resource allocation and social relationships, global examples from countries like Finland and Canada demonstrate the effectiveness of inclusive policies and practices. Implementing inclusive education benefits not only students with disabilities but enriches the learning experience for all, paving the way for a fair and inclusive society.